SOME FACTORS RELATED TO THE SEVERITY OF PNEUMONIA IN CHILDREN UNDER 5 YEARS OLD WITH RSV INFECTION AT TUYEN QUANG PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze factors associated with the severity of pneumonia among children under five years of age treated at the Pediatrics Department, Tuyen Quang provincial General Hospital, during 2024-2025.Subjects and methods: A cross-sectional descriptive study was conducted on 220 children aged 0 to 59 months who were diagnosed with pneumonia according to the 2014 WHO criteria and had confirmed RSV infection (positive RSV rapid test) from July 2024 to June 2025.Results: Independent factors associated with an increased risk of severe pneumonia in children under five years of age with RSV infection included: age < 12 months (OR = 21.44; 95% CI: 6.07-75.86; p < 0.001), wheezing (OR = 2.32; 95% CI: 1.17-4.62; p = 0.016), anemia (OR = 2.10; 95% CI: 1.04-4.52; p = 0.049), and congenital heart disease (OR = 7.80; 95% CI: 1.13-57.20; p = 0.041).Conclusions: Age under 12 months, wheezing, anemia, and congenital heart disease are independent risk factors associated with severe pneumonia in children under five years of age with RSV infection at Tuyen Quang provincial General Hospital.
Keywords: Pneumonia with RSV infection, related factors, children under 5 years old.